Nurses' knowledge, attitudes and practices related to physical restraint: the case from Turkey - Selen OZAKAR AKCA; Ahu Pınar TURAN (Universa Medicina, 2023)
BackgroundNurses are primarily for the care of patients and should ensure that physical restraint, which has many negative consequences, be applied according to standard practice. Therefore, they should have knowledge about physical restraint and apply physical restraint by observing existing laws and ethical principles. This study aimed to determine the knowledge level, attitude and practices of pediatric nurses on physical restraint and identify the factors influencing physical restraint use. MethodsA cross-sectional study was conducted involving 150 pediatric nurses working in the pediatric clinic of a training and research hospital. The data were collected with an information form containing the introductory characteristics of the nurses and the Level of Knowledge, Attitudes and Practices of Staff Regarding Physical Restraints Questionnaire. Data were analyzed using the Mann-Whitney U test and the Kruskal-Wallis test. ResultsOverall, nurses had good restraint-related knowledge with positive attitudes, although the physical restraint practices of nurses were not the best and there were some deficiencies. A statistically non-significant difference was found between age, gender, education status, nurses' work unit, and training status regarding physical restraint on the one hand and knowledge, attitude and practice scores relating to the use of physical restraints on the other (p>0.05). ConclusionsPediatric nurses' level of knowledge about physical restraint was quite good and their attitudes were positive. However, there were some deficiencies in their practices. Future training should therefore be emphasized to enhance nurses' ethical and sensitive thinking, increase their competence in applying physical restraint and working with patients.